A New Approach for Vehicle Lateral Velocity and Yaw Rate Control with Uncertainty. Issue 1 (24th May 2017) - Sun, Hao; Zhao, Han; Huang, Kang; Zhen, Shengchao
Abstract: In order to attain excellent stability and maneuverability to ensure safety and ride‐comfort, the lateral velocity and yaw rate of a vehicle are expected to be controlled at any desired values simultaneously. A basic manipulation model of a vehicle with two degrees of freedom which requires two independent control inputs (front and rear steering angle) is constructed. In this model, we consider the mass and the moment of inertia of the vehicle are the uncertain parameters which are (possibly) fast‐varying. However, no further information, except that the uncertainties are bounded, is assumed. Furthermore, the bound is unknown. An adaptive robust control methodology based on the Udwadia and Kalaba approach which guarantees uniform boundedness and uniform ultimate boundedness is proposed to drive the system to follow the pre‐specified constraints approximately. The adaptive law is of leakage type which can adjust itself based on the tracking error. The numerical simulation results conducted byMATLAB demonstrate the ease and effectiveness of implementation.